2000
DOI: 10.1161/01.str.31.9.2231
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Estrogen on Leukocyte Adhesion After Transient Forebrain Ischemia

Abstract: Background and Purpose-Recent findings indicate that estrogen (ie, 17␤-estradiol [E 2 ]) provides neuroprotection in models of transient global and focal ischemia. Enhanced postischemic leukocyte adhesion and infiltration have been linked to neuropathology in the brain as well as other tissues. We recently showed that estrogen reduces leukocyte adhesion in the cerebral circulation of female rats during resting conditions. Methods-We compared leukocyte adhesion in pial venules in vivo in intact, ovariectomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
80
0
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 30 publications
4
80
0
2
Order By: Relevance
“…In hypercholesterolemic rabbits, monocyte adhesion to endothelial cells and transendothelial migration is retarded in females compared with male animals; an effect likely due to female sex hormone activity since ovariectomy enhances cell adhesion while supplementation of these animals with 17b-estradiol restores protection (Nathan et al 1999). This protective effect of sex is reproduced in other inflammatory models, again including ischemia-reperfusion injury, where, for instance, female sex hormones decrease leukocyte adhesion in response to a transient forebrain ischemic insult (Santizo et al 2000). In addition, 17b-estradiol reduces the granulocyte and monocyte/macrophage populations of injured vessels and limits leukocyte entry from adventitial/ periadventitial tissues into injured vessels, thereby reducing the neointimal response to vascular injury .…”
Section: Sex Differences In Leukocyte Recruitmentmentioning
confidence: 99%
“…In hypercholesterolemic rabbits, monocyte adhesion to endothelial cells and transendothelial migration is retarded in females compared with male animals; an effect likely due to female sex hormone activity since ovariectomy enhances cell adhesion while supplementation of these animals with 17b-estradiol restores protection (Nathan et al 1999). This protective effect of sex is reproduced in other inflammatory models, again including ischemia-reperfusion injury, where, for instance, female sex hormones decrease leukocyte adhesion in response to a transient forebrain ischemic insult (Santizo et al 2000). In addition, 17b-estradiol reduces the granulocyte and monocyte/macrophage populations of injured vessels and limits leukocyte entry from adventitial/ periadventitial tissues into injured vessels, thereby reducing the neointimal response to vascular injury .…”
Section: Sex Differences In Leukocyte Recruitmentmentioning
confidence: 99%
“…[12][13][14] Additionally, and of relevance to central nervous system (CNS) autoimmune disease, a direct neuroprotective effect of E2 has also been demonstrated. [15][16][17] These effects of estrogen are mediated through specific receptors and depend on regulated expression and cellular distribution of these receptors. 18 We have shown recently that estrogen receptor-␣ (Esr1) is crucial for the beneficial therapeutic effect of 17␤-estradiol (E2) in murine experimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis.…”
mentioning
confidence: 99%
“…In fact, there is currently no consensus on the magnitude or pathologic role of leukocyte adhesion in nonskeletal tissues after OVX. OVX has been reported to enhance PMN accumulation in the brain of resting animals (Santizo et al, 2000) but other data indicated that OVX does not influence the PMN adherence in the brain tissue after transient ischemia (Xu et al, 2004). We suggest that these differences in baseline leukocyte adhesion might be explained by the different timelines.…”
Section: Discussionmentioning
confidence: 64%
“…In our model, typical reactions after OVX, such as weight gain and osteopenia, reproducibly evolved, and the reversing efficacy of E2 therapy on osteopenia, together with the periosteal microcirculatory status of the tibia, could subsequently be evaluated in a clinically relevant, long-term period. OVX-related vascular alterations have already been demonstrated in certain organs (Santizo RA 2000;Watanabe Y 2001), but never in the periosteum. For instance, OVX has reduced the blood flow in the bone (Kapitola J 1995) and a lower total capillary density was observed in the heart (Jesmin S 2002) and brain (Jesmin S 2003), a phenomenon probably related to the well-known effect of oestrogen on angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation